Manajemen Business Cycle Sebagai Basis Peluang Usaha Pasca Covid-19 : Suatu Strategi Pemulihan Ekonomi Masyarakat - Asmini Asmini; I Nyoman Sutama; Wahyu Haryadi; Rosydah Rachman (Indonesian Journal of Social Sciences and Humanities, 2020)
This study aims to describe the management of the business cycle as a basis for post Covid-19 business opportunities. This descriptive study uses the study of documents. The data in this study were sourced from secondary data in the form of documents or archives, published notes related to the business cycle data in Indonesia during Covid-19. Data were then analyzed using reference/text analysis techniques. Based on the analysis of business cycle management or business cycle management through the process of planning and organizing business cycles in four periods that can describe the classification of business types in the business sector or post Covid-19 business opportunities. In total, of the four business cycle periods, there were 61 businesses with 33 types of businesses in the peak cycle period, as many as 8 types of business in the economic recession period, 14 types of businesses in the most severe period of depression, and 6 other types of business in the recovery period (expansion ). The business cycle has also been categorized by type of business in five business sectors, with the largest being in the service business type. In general, business cycle management is needed as a basic basis for post-Covid-19 business opportunities to become a community economic recovery strategy.